Activation of E–H and E–E (E = S, O) Bonds by Heterobimetallic Zr/Co Complexes: Evidence for Both One‐ and Two‐Electron Processes. Issue 22 (22nd May 2013) - Napoline, J. Wesley; Krogman, Jeremy P.; Shi, Rena; Kuppuswamy, Subramaniam; Bezpalko, Mark W.; Foxman, Bruce M.; Thomas, Christine M.
Abstract: The reactivity of the reduced Zr III Co 0 heterobimetallic complex [(thf)Zr(MesNP i Pr2 )3 CoN2 ] (1a ) towards O–H, S–H, S–S, and O–O bonds has been investigated. Complex1a reacts readily with PhOH, EtOH, and H2 O to generate the one‐electron‐oxidized complexes [(RO)Zr(MesNP i Pr2 )3 CoN2 ] [R = Et (2 ), Ph (3 ), H (4 )]. In contrast, PhSH and PhS–SPh react by means of overall two‐electron processes to form [(η 2 ‐MesNP i Pr2 )Zr(μ‐SPh)(MesNP i Pr2 )2 Co(SPh)] (5a ). Addition of stoichiometric diethyl peroxide to1a generates2, but further equivalents lead to the two‐electron oxidized product [(EtO)Zr(MesNP i Pr2 )3 Co(OEt)] (6 ). More sterically hindered peroxides such as dicumyl peroxide or di‐ tert ‐butyl peroxide do not react with1a under ambient conditions, but upon photolysis, di‐ tert ‐butyl peroxide reacts with1a to form [( t BuO)Zr(MesNP i Pr2 )3 CoN2 ] (7 ). These results imply that an inner‐sphere electron‐transfer process is occurring at the Zr site of1a upon treatment with these chalcogen‐based substrates, and a dissociative electron‐transfer mechanism is proposed. Abstract : A highly reactive phosphanylamide‐supported Zr/Co complex has been shown to react with alcohols, thiols, peroxides, and disulfides by means of a dissociative electron‐transfer process occurring at Zr. A range of products are formed depending on the identity of the substrate, including both one‐ and two‐electron oxidized products.